Influence of Acarbose on Blood Glucose and Breath Hydrogen after Carbohydrate Load with Sucrose or Starch - Koytchev, Rossen; Richter, Wolfram; Erkent, Ülkem; Kirkov, Valentin; Dimitrova, Velislava; Nern, Andreas; Runter, Ulrich (Arzneimittelforschung, 2009)
A monocentric, open, randomised, single-dose, six-period crossover trial was carried out in healthy volunteers under fasting conditions to establish the most appropriate study design for a pivotal bioequivalence trial with acarbose (CAS 56180-94-0) regarding a) dosage of the drug, b) type of carbohydrate load, c) type of primary endpoint, and d) sample size. 50 g sucrose or 50 g starch were used as carbohydrate load. Acarbose was administered in doses of 50 and 200 mg. Blood glucose and breath hydrogen were evaluated as endpoints. Both acarbose doses reduced the effect of carbohydrate load. Blood glucose: no statistically significant difference could be noted between the overall effect of 50 mg and that of 200 mg acarbose irrespective of the type of carbohydrate load. Breath hydrogen: an influence could be shown only for sucrose as carbohydrate load. Practically no effect was observed with starch. The overall increase of effect is by more than 200% with sucrose when the dose of acarbose increases from 50 to 200 mg. This difference between the effects of both doses of acarbose on breath hydrogen is statistically significant. For a pivotal trial, sucrose is the most appropriate type of carbohydrate load, baseline adjusted area under the breath hydrogen response is the most appropriate primary endpoint, and a dose of 100 mg acarbose is the most appropriate dosage. A total number of 100 subjects will be needed for proving pharmacodynamic equivalence between two acarbose products in a pivotal trial.
Keywords: Acarbose; Blood glucose; Breath hydrogen; Carbohydrate load; CAS 56180-94-0; Starch; Sucrose